The Effect of Graphite and Fe2O3 Addition on Hydrolysis Kinetics of Mg-Based Hydrogen Storage Materials - Kun Yang; Hongyun Qin; Junnan Lv; Rujun Yu; Xia Chen; Zengdian Zhao; Yongjie Li; Fang Zhang; Xianchang Xia; Qiang Fu; Ming Wang (International Journal of Photoenergy)
In this paper, graphite and Fe2O3 are introduced into MgH2 powder by the method of hydrogenation after magnetic grinding. Hydrogen storage materials which composite of MgH2–5 wt.% C and MgH2–5 wt.% C–5 wt.% Fe2O3 are successfully prepared. The physical structure of these materials was analyzed and characterized by XRD, SEM, etc. Furthermore, the influence of graphite and Fe2O3 on the hydrolysis of MgH2 was systematically investigated. The results show that MgH2–C–Fe2O3 composite powder has the fastest hydrogen release rate in municipal drinking water and the highest conversion rate. Graphite and Fe2O3 can effectively reduce the activation energy of the hydrolysis reaction of MgH2 and improve the hydrolysis kinetics of MgH2. The synergistic effect of the coaddition of graphite and Fe2O3 can significantly increase the hydrolysis conversion rate of MgH2 and improve the hydrolysis kinetics.